Implementation of Gesture Alert and Health Assistance System for Physically Disabled Using Internet of Things (Iot) - Neha Mangla Vidyavarshini H J, Dr; ., . (International Journal of Engineering and Technology, 2018)
Gesture based monitoring for assisted living is gaining importance and attention, especially to facilitate physically disabled and the elderly citizens[2],[3] by examining their health and movements, which otherwise could lead to a collapse or a fall. It is quite a challenge for the nursing and care taker staff to constantly monitor the patients and assist them at all times. This can be overcome by the help of a device that is multi-functional and portable enough to place it on any piece of furniture. An integration of health assistance [13] and gesture alert is a very comprehensive approach to increase the potential future of health monitoring. An application context for health monitoring and gesture alert can be therefore developed with lower costs, a system that is robudt and also reduces the number of devices to be worn by a patient. A Patient Monitoring System (PMS) and various wearable devices [23] act as pioneers to establish a safer and a healthier world.Â Â